Abiotic and biotic factors influence diapause induction in sexual and asexual strains of Trichogramma brassicae (Hym: Trichogrammatidae). Issue 1 (December 2018) - Rahimi-Kaldeh, Somayeh; Ashouri, Ahmad; Bandani, Alireza; Ris, Nicolas
Abstract The effects of some abiotic (maternal photoperiod and offspring developmental temperature) and biotic (host quality during both maternal and offspring generations) factors on diapause induction were investigated for two sympatric strains ofTrichogramma brassicae Bezdenko (Hym: Trichogrammatidae) differing by infection status with regard toWolbachia . The mode of reproduction, developmental temperature, maternal photoperiod and the quality of the host significantly affected diapause induction. The highest percentage of diapausing individuals were observed with the sexual strain reared at 14 °C using a "high quality" host and after a long photophase during the maternal generation. Environment-by-Environment, as well as Genotype-by-Environment interactions, was observed. All these patterns were discussed with the goal of providing relevant protocols for the commercial mass-rearing of such biocontrol agents. A successful diapause in beneficial insects could affect the efficiency of mass rearing by increasing the duration of storage conditions based on a high percent emergence and providing a large number of individuals at the appropriate time in the field season.